Proteotranscriptomics reveals the secretory dynamics of teratocytes, regulators of parasitization by an endoparasitoid wasp - Pinto, Ciro P.G. [UNESP]; Walker, Andrew A.; Robinson, Samuel D.; King, Glenn F.; Rossi, Guilherme D. [UNESP] (Elsevier, 2022)
Parasitoid wasps have evolved sophisticated mechanisms of host regulation that establish a favorable environment for the development of immature parasitoids. While maternal venom and symbiotic virus-like particles are well-known mechanisms of host regulation, another less-studied mechanism is the secretion of host regulation factors by cells called teratocytes, extra-embryonic cells released during parasitoid larval eclosion. Consequently, identification and characterization of teratocyte secretory products has not been reported in detail for any parasitoid wasp. We aimed to analyze teratocyte secretory products released into hemolymph of the larval sugarcane borer Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) by its biological control agent, the koinobiont endoparasitoid wasp Cotesia flavipes Cameron, 1891 (Hymenoptera: Braconidae). Teratocytes were released upon eclosion of parasitoid larvae four days after parasitization (DAP) and increased in number and size until six DAP. Total D. saccharalis hemocyte viability was reduced immediately after parasitization until DAP 2, while total hemocyte count was lower from the third DAP, and phenoloxidase and lysozyme activity were disrupted compared to non-parasitized controls. To examine the secretory products of teratocytes, we generated a teratocyte transcriptome and compared its in silico translated open reading frames to mass spectra obtained from hemolymph from parasitized and unparasitized hosts. This led to the identification of 57 polypeptides secreted by teratocytes, the abundance of which we tracked over 0–10 DAP. Abundant teratocyte products included proteins similar to bracovirus proteins and multiple disulfide-rich peptides. Most teratocyte products accumulated in hemolymph, reaching their highest concentrations immediately before parasitoid pupation. Our results provide insights into host regulation by teratocytes and reveal molecules that may be useful in biotechnology.
Keywords: Biological control; Defensin; Immune system; Lysozyme; Peptide; Phenoloxidase